Digital-assisted diagnosis and orthodontic management of an impacted mandibular lateral incisor: a case report - Jingwen Cai; Sihang Chen; Linxin Chen; Xinhan Yang; Xiran Dai; Zhenzhen Dai; Linyu Xu (BMC, 2024)
Abstract Background The impaction of mandibular lateral incisors presents significant aesthetic and functional challenges in orthodontics, including Bolton ratio discrepancies and anterior occlusal anomalies. The increasing preference for nonextraction treatment further complicates space management within the dental arch. However, the advent of digital-assisted orthodontic technologies, particularly advanced digital simulations, has revolutionized the precision and effectiveness of diagnosis and treatment planning. These technologies enable clinicians to strategically leverage natural jaw development and create the necessary space for the alignment of impacted teeth without resorting to extraction. Case presentation This case report details the treatment of a 12-year-old male with an impacted mandibular lateral incisor, which resulted in both aesthetic concerns and functional impairments, alongside Class II malocclusion. By employing a digital-assisted diagnostic approach, including comprehensive digital simulations, we meticulously evaluated the feasibility of a nonextraction treatment plan. The strategy centred on harnessing the patient's mandibular growth potential to expand the available space naturally. The treatment involved surgical exposure of the impacted tooth, followed by precise orthodontic traction guided by continuous digital monitoring. The integration of digital tools throughout the treatment process was crucial in achieving successful eruption and alignment of the impacted tooth, thus restoring optimal aesthetics and function without the need for extraction. Conclusion This case highlights the transformative impact of digital-assisted technologies in the management of complex orthodontic cases, such as impacted mandibular lateral incisors. The successful integration of these advanced tools with a nonextraction treatment approach underscores their potential to significantly enhance clinical outcomes. Digital technologies not only improve the accuracy and effectiveness of treatment but also facilitate a multidisciplinary approach that elevates the standard of patient care in addressing complex orthodontic challenges.